Trauma Surgeon and Palliative Care Physician Attitudes Regarding Goals-of-Care Delineation for Injured Geriatric Patients. (August 2019) - Cunningham, Holly B.; Scielzo, Shannon A.; Nakonezny, Paul A.; Bruns, Brandon R.; Brasel, Karen J.; Inaba, Kenji; Brakenridge, Scott C.; Kerby, Jeffrey D.; Joseph, Bellal A.; Mohler, M. J.; Cuschieri, Joseph; Paulk, Mary E.; et al.
Background: The value of defining goals of care (GoC) for geriatric patients is well known to the palliative care community but is a newer concept for many trauma surgeons. Palliative care specialists and trauma surgeons were surveyed to elicit the specialties' attitudes regarding (1) importance of GoC conversations for injured seniors; (2) confidence in their own specialty's ability to conduct these conversations; and (3) confidence in the ability of the other specialty to do so. Methods: A 13-item survey was developed by the steering committee of a multicenter, palliative care-focused consortium and beta-tested by trauma surgeons and palliative care specialists unaffiliated with the consortium. The finalized instrument was electronically circulated to active physician members of the American Association for the Surgery of Trauma and American Academy for Hospice and Palliative Medicine. Results: Respondents included 118 trauma surgeons (8.8%) and 244 palliative care specialists (5.7%). Palliative physicians rated being more familiar with GoC, were more likely to report high-quality training in performing conversations, believed more palliative specialists were needed in intensive care units, and had more interest in conducting conversations relative to trauma surgeons. Both groups believed themselves to perform GoC discussions better than the other specialty perceived them to do so and favored their own specialty leading team discussions. Conclusions: Both groups believe themselves to conduct GoC discussions for injured seniors better than the other specialty perceived them to do so, which led to disparate views on the optimal leadership of these discussions.